Pineal Neurosteroids: Biosynthesis and Physiological Functions - Haraguchi, Shogo; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2020)
Similar to the adrenal glands, gonads, and placenta, vertebrate brains also produce various steroids, which are known as “neurosteroids.” Neurosteroids are mainly synthesized in the hippocampus, hypothalamus, and cerebellum; however, it has recently been discovered that in birds, the pineal gland, a photosensitive region in the brain, produces more neurosteroids than other brain regions. A series of experiments using molecular and biochemical techniques have found that the pineal gland produces various neurosteroids, including sex steroids, de novo from cholesterol. For instance, allopregnanolone and 7α-hydroxypregnenolone are actively produced in the pineal gland, unlike in other brain regions. Pineal 7α-hydroxypregnenolone, an up-regulator of locomotion, enhances locomotor activity in response to light stimuli in birds. Additionally, pineal allopregnanolone acts on Purkinje cells in the cerebellum and prevents neuronal apoptosis within the developing cerebellum in juvenile birds. Furthermore, exposure to light during nighttime hours can cause loss of diurnal variations of pineal allopregnanolone synthesis during early posthatch life, eventually leading to cerebellar Purkinje cell death in juvenile birds. In light of these new findings, this review summarizes the biosynthesis and physiological functions of pineal neurosteroids. Given that the circadian rhythms of individuals in modern societies are constantly interrupted by artificial light exposure, these findings in birds, which are excellent model diurnal animals, may have direct implications for addressing problems regarding the mental health and brain development of humans.